PERAN KEMENDAGRI DALAM PENUNJUKKAN KEPALA DAERAH SEBAGAI KETUA PENANGANAN PANDEMI COVID-19 JAKARTA - Immanuel Ignatius; Reni Dwi Purnomowati (Reformasi Hukum Trisakti, 2022)
The President receives assistance from the Ministry of Home Affairs (Kemendagri) in managing the Covid-19 distribution. The formulation of the issue is a means of establishing authority for the appointment of Task Force Officers for the Acceleration of Handling Corona Virus Disease 2019 (Covid-19) in accordance with Presidential Decree Number 7 of 2020 and Minister of Home Affairs Circular Letter Number 440/2622/SJ, as well as the Ministry of Home Affairs' attempts to remove barriers that Regional Leaders faced in carrying out the Acceleration Management of Corona Virus Disease 2019 (Covid-19) in DKI Jakarta. Using secondary data for descriptive analysis and qualitative deductive reasoning, the research method is juridical-normative. Research findings, analysis, and conclusions: The Ministry of Home Affairs' involvement in appointing Regional Leaders to delegate authority can hasten the management of the COVID-19 epidemic while still giving due consideration to the economic issue. Regional leaders be able to carry out plans that strike a balance between economic and health-related considerations as executors of regional government issues. Making Joint Decrees of the Ministers of Home Affairs and Finance Number 119/2813/SJ and Number 117/KMK.07/2020 focused on health, social assistance, and saving the economy in their respective regions, notably MSMEs, is being attempted.